Banking Laws v. III: Africa part two - Statistical Economic and Social Research and Training Centre for Islamic Countries Organisation of the Islamic Conference (Ankara, Turkey SESRTCIC Publications, 1993)
The book contains laws governing commercial and central banks as well as overall financial and banking systems in the following countries: Algeria, Benin, Burkina Faso, Chad, Djibouti, Egypt, Gabon, Gambia, Guinea, Jamahiriya, Mali, Mauritania, Morocco, Nigeria, Sierra Leone, Somalia, Sudan, Tunisia, Uganda, and West African Monetary Union.
osc 18/8/16
Loans
Keywords: Banking Law